Genetic Effects for Plasma Factor VII Levels Independent of and in Common with Triglycerides - Hong, Yuling; Pedersen, Nancy L.; Egberg, Nils; Faire, Ulf de (Thrombosis and Haemostasis, 1999)
Background. Coagulation factor VII has been demonstrated as a potential risk factor for cardiovascular disease. Both genes and non-genetic factors are related to plasma levels of factor VII. However, the extent to which genetic effects influence variability in plasma factor VII levels is unknown. Further, increased levels of plasma factor VII are associated with serum triglycerides, yet the reason for this association is not fully understood. Methods and Results. Quantitative genetic analyses were applied to evaluate the relative importance of genetic and different environmental influences on plasma factor VII levels and to test the significance of genetic and environmental factors in common to factor VII and triglycerides in 215 pairs of middle-aged and elderly twins, of whom 104 were reared apart and 120 were women. Genetic influences were found to account for 57% of the individual differences in plasma factor VII levels, whereas shared-rearing and residual-familial environmental factors were not significant. Furthermore, a significant genetic correlation of 0.38 was found between factor VII and triglycerides, but the environmental correlation between these two measures was not significant. Genetic factors in common to factor VII and triglycerides explain about 7% of the total variance for factor VII. Conclusion. The present study suggests that there are substantial genetic influences on plasma factor VII levels. Furthermore, genetic effects explain the phenotypic association between factor VII and triglycerides.